The Influence Factors of Psychological Understanding and Behavior Choice for Legal Industry Entrepreneurs Based on Artificial Intelligence Technology - Miao, Zeyi (Frontiers in Psychology, 2020)
This study is aimed to promote China’s support for innovation and entrepreneurship in the context of the rapid development of the artificial intelligence industry. Considering the advance law-based governance implemented in this country, the relationship between the psychological understanding and behavior choice of entrepreneurs in the law industry and artificial intelligence industry was explored. The investigation was conducted in the form of questionnaire survey, and the data was collected by sending emails. Also, the model was established to make the investigation direction clearer. The reliability analysis of the questionnaire was carried out by means of Cronbach α reliability coefficient. The validity analysis of the questionnaire was carried out by KMO (Kaiser-Meyer-Olkin) coefficient. The statistical software was used to analyze the correlation between the factors in the investigation. The results show that there is a positive correlation between behavior speed in the psychological understanding of entrepreneurs in the legal industry as well as the entrepreneurial experience and entrepreneur behavior. The concentration of entrepreneurs’ behavior is negatively correlated with the entrepreneur’s industrial experience. The behavior speed and concentration of entrepreneurs in the artificial intelligence industry are negatively correlated with the age of entrepreneurs, but their entrepreneurial behavior and psychological understanding do not show correlation. The behavior speed and concentration of entrepreneurs in the artificial intelligence industry are positively correlated with product innovation, technological innovation, and market innovation. Therefore, the behavior choice of entrepreneurs in the legal industry are highly correlated with psychological understanding. The entrepreneurs’ psychological understanding and behavior choice in the field of artificial intelligence do not show a direct correlation, but indirect correlation through indirect factor innovation opportunities. The investigation on entrepreneurs’ psychological understanding and behavior choice can provide important theoretical support for entrepreneurs in China’s legal industry and artificial intelligence industry.